KOMUNIKASI TERAPEUTIK TERHADAP ANAK YANG TAKUT BEROBAT GIGI - Annisa, Nurul; Qalbi, Astri Annur; Eni, St. Nur; Magfirah, Febi (Jurnal Ilmiah Amanah Akademika, 2023)
method used in this study uses a library research approach and method. Literature or literature studies can be interpreted as a series of activities related to using library data collection methods, reading and recording and processing research materials. The content of the material presented is effective communication for children who are afraid of dental treatment. Most people, maybe even ourselves, give priority to dental health, especially children who are afraid of dental treatment. Children's negative perception of dental treatment can cause fear that can cause children to refuse dental treatment. This can also be due to the child's experience before getting dental treatment or visiting the dentist, environmental influences, the influence of the attitude of their parents or family towards them. The world of health is increasingly prioritizing communication in healing methods that can support the recovery of patients. This study aims to determine the effect of giving therapeutic communication to children who are afraid of dental treatment.